Cultural Differences in School Success - Hasekiu, Fitnet (Richtmann Publishing, 2012)
In Albania live together many ethnical groups and one of them is Roma ethnical group. The main focus in this article is theidentification of cultural differences in school success. The data in this study are collected through naturalistic observation and survey. Itis observed that Roma students have lower success in school than Albanian students. I have studied this phenomenon extensively andhave come up with some explanations. When Albanian students enter school, they enter ready – academically, socially, and emotionally– to learn in the school environment. Their parents have read to them since they were infants, so books are familiar friends. They havehad experiences sharing toys with other children and have been trained how to handle conflicts in a nonaggressive manner. Not so formany Roma students, who came from a different culture – the culture of the streets. Their parents are forced to prepare them to survivelife on the street of the city, rather than to read and write in a classroom. They may not even have seen a picture book before, much lesslistened as someone read to them. They may never had a chance how to work cooperatively with others or share – they may not havehad many toys to share.